Pengaruh Beban Kerja Dan Stres Kerja Terhadap Dinamika Budaya Kerja Pegawai Universitas Nias (Jurnal Ilmu Sosial Dan Politik, 2025)
This study analyzes the influence of workload and work stress on the work culture of Nias University employees. The method used is quantitative with multiple regression analysis. The results show that workload has a significant effect on work culture with a contribution of 77.9%, work stress has a significant effect with a contribution of 30.5%, and simultaneously both have an effect of 79.8%. In conclusion, workload and work stress have a strong effect on the work culture of Nias University employees, so management strategies are needed in the form of balanced work distribution, managerial support, and the creation of a positive work environment to form a healthy and productive work culture.